2010
DOI: 10.1007/s12272-010-0804-2
|View full text |Cite
|
Sign up to set email alerts
|

Two new dihydrofuranoisoflavanones from the leaves of Lespedeza maximowiczi and their inhibitory effect on the formation of advanced glycation end products

Abstract: Two new dihydrofuranoisoflavanones, 2',4',5-trihydroxy-[5''-(1,2-dihydroxy-1-methylethyl)-dihydrofurano(2'',3'':7,8)]-(3S)-isoflavanone (1) and 2', 4', 5-trihydroxy-[5''-(1,2-dihydroxy-1-methylethyl)-dihydrofurano(2'',3'':7,8)]-(3R)-isoflavanone (2) as well as one already-known compound, (+)-catechin (3), were isolated from an n-BuOH soluble fraction from the leaves of Lespedeza maximowiczi. Spectroscopic data was used to elucidate the structures of compounds 1 and 2. All of the isolates were evaluated in vitr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
(16 reference statements)
0
10
0
Order By: Relevance
“…Woo et al reported that root bark of LB contained significant bacterial neuraminidase inhibitory activity [18]. It has recently been demonstrated that Lespedeza species can protect pancreatic β-cells from cytokine-induced damage in streptozotocin-induced diabetic mice [19,20], inhibit the formation of AGEs [21], and ameliorate endothelial dysfunction arising from MGO-induced glucotoxicity in diabetic retinopathy mode [13]. Chemical composition from LB extract includes stigmasterols, organic acids, terpenes, alkaloids, and flavonoids that have been screened for anticancer, anti-radiation, antioxidant, reducing blood sugar, and anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Woo et al reported that root bark of LB contained significant bacterial neuraminidase inhibitory activity [18]. It has recently been demonstrated that Lespedeza species can protect pancreatic β-cells from cytokine-induced damage in streptozotocin-induced diabetic mice [19,20], inhibit the formation of AGEs [21], and ameliorate endothelial dysfunction arising from MGO-induced glucotoxicity in diabetic retinopathy mode [13]. Chemical composition from LB extract includes stigmasterols, organic acids, terpenes, alkaloids, and flavonoids that have been screened for anticancer, anti-radiation, antioxidant, reducing blood sugar, and anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%
“…Note this is three times greater than the IC 50 of Onco A (87.88 ± 3.08 μM). Park et al [ 24 ] have reported that three compounds isolated from Lespedeza maximowiczi are actually more active than Onco A, with IC 50 values ranging from 5.4–20.6 μM.…”
Section: Resultsmentioning
confidence: 99%
“…As a physiologically active substance of L. cuneata G. Don, β‐sitosterol, quercetin, kaempferol, pinitol, avicularin, juglanin, and trifolin (Matsuura, Iinuma, Ito, Takami, & Kagei, ) have been identified. In addition, the hot water and ethanol extract of L. cuneata G. Don have been reported to have antioxidative effect through its flavone glycosides (Deng, Chang, & Zhang, ; Park, Kim, & Kwon, ). Even though there are a rich of the natural biological resource in L. cuneata G. Don, the specific study on the potential of the cosmeceutical composition using L. cuneata G. Don is still insufficient.…”
Section: Introductionmentioning
confidence: 99%